PERSISTENCE OF CRYSTAL-PRODUCING INSECTICIDAL BACTERIA ON THE LEAVES OF APPLE TREE (Proceedings of the YSU B: Chemical and Biological Sciences, 2023)
Persistence of entomopathogenic bacteria on the leaves of apple tree after spray has been studied. By experimental data it was established that insecticidal strains are maintained no more than two months, without losing their ability to produce spores and entomocide crystals.
Keywords: Persistence of entomopathogenic bacteria; leaves of apple tree; spores; entomocide crystals